2019
DOI: 10.1002/slct.201803611
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Chemi‐adsorption, EDLC, and Redox Capacitance Through Electro‐precipitation Synthesis of Fe3O4/NiO@rGO/h‐BN for the Development of Hybrid Supercapacitor

Abstract: 3D Fe3O4/NiO was grafted on to the 2D rGO/h‐BN by electro‐precipitation method. Nitrogen of h‐BN moiety and oxygen functional groups of rGO played the role of negative active site to trap the metallic cations. Electrochemical charge storage mechanism was optimized by controlling the stoichiometry and defect contents of Fe3O4/NiO@rGO/h‐BN. Stoichiometry of the electro‐precipitated samples was tailored in presence of negative active sites of rGO/h‐BN and applied D.C. bias of the electrochemical bath. In addition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 47 publications
0
5
0
Order By: Relevance
“…The energy density and power density of MoS 2 melt 5 mPP were 64.31 W h kg −1 and 3858.42 W kg −1 at the current density of 0.57 A g −1 , and were calculated by using the relations 92–94 given in eqn (6) and (7), respectively.where E = specific energy density (W h kg −1 ), Δ V = potential window, C s = specific capacitance.where P = power density (W kg −1 ), E = specific energy density (W h kg −1 ), t = discharge time.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The energy density and power density of MoS 2 melt 5 mPP were 64.31 W h kg −1 and 3858.42 W kg −1 at the current density of 0.57 A g −1 , and were calculated by using the relations 92–94 given in eqn (6) and (7), respectively.where E = specific energy density (W h kg −1 ), Δ V = potential window, C s = specific capacitance.where P = power density (W kg −1 ), E = specific energy density (W h kg −1 ), t = discharge time.…”
Section: Resultsmentioning
confidence: 99%
“…The energy density and power density of MoS 2 melt 5 mPP were 64.31 W h kg −1 and 3858.42 W kg −1 at the current density of 0.57 A g −1 , and were calculated by using the relations [92][93][94] given in eqn ( 6) and (7), respectively.…”
Section: Electrochemical Studies Cyclic Voltammetry (Cv)mentioning
confidence: 99%
“…[48][49][50] Yuan et al prepared all-solid-state SC using Mn-doped NiMoO 4 and reduced graphene oxide (rGO) composite by heating metal salts with GO at 160°C for 8 h as shown in Figure 1(a). [51] Oxygen functionalities on the GO anchored the metal salts by electrostatic attraction and promoted the growth [141] NiÀ Co hydroxide@rGO 180°C for 12 h L-ascorbic acid, KOH [142] CNT@NiÀ Co double hydroxide nanoneedles 220°C for 24 h Urea [143] Functional porous Carbon/NiO 100°C for 10 h, annealing at 900°C under N 2 CTAB, NH 4 OH [82] NiCo 2 O 4 /Carbon nanofiber 90°C for 4 h, calcination at 350°C under air HMTA [144] NiCo 2 O 4 @polydopamine modified poplar catkins 120°C for 6 h, annealing at 300°C under air HMTA, Citric acid trisodium salt [88] ZnFe 2 O 4 /N-modified Graphene 180°C for 12 h, annealing at 250°C - [145] Electrodeposition Fe 3 O 4 /NiO@rGO/hexagonal-Boron nitride metal ions electroprecipitated on rGO/h-BN then calcined at 500°C - [80] CNT-Fe 3 O 4 -rGO rGO deposited on CNTÀ Fe3O4 film by electrophoresis LiClO 4 electrolyte solution [146] Mn-doped NiCo-LDH coated porous carbon electropolymerization and annealing of PANI on carbon cloth, electrodeposition of metals Polyaniline (PANI) carbon source [57] CC/Carbon fibers/NiCo 2 O 4 NiCo 2 O 4 electrodeposited on CF pre-deposited on CC by CVD method - [147] NiOx-CNT-NiCo 2 O 4 NiCo NPs and CNT co-deposited on Ni foam by electrophoresis catalytic amount of Ni + 2 [89] CNT/NiCo 2 O 4 core-shell structure NiCo 2 O 4 electrodeposited on CNT pre-deposited on stainless steel foil - [90] 3D Ni foam/N-doped CNT/ NiCo 2 O 4 NSs NiCo 2 O 4 electrodeposited on N-CNT pre-deposited on Ni foam, then annealed at 300°c in air - [148] r-GO/MnO 2 electrodeposited on stainless steel, annealing at 300°C - [53] Physical mixing MnOx-Carbon dots-Graphene nanocomposites CDs-Graphene solution mixed with KMnO 4 at 75°C - [60] Mesoporous 3D NiCo 2 O 4 /MWCNT aerogels supercritical CO 2 drying of gel containing metal ions Epichlorohydrin gelation agent [72] Ni/CNT/MnO 2 MnO 2 on Ni fiber dip coated with CNT followed by drying and washing - [149] CdS-CoFe 2 O 4 @rGO nanohybrid pre-synthesized CdS-CoFe mixed with rGO solution and heated in oil bath NH 4 OH, Hydrazine [150] CuÀ MOF/rGO composite ultrasonic mixing o...…”
Section: Hydrothermal/solvothermal Methodsmentioning
confidence: 99%
“…Consequently, Saha et al recently reported 3D Fe 3 O 4 /NiO embedded on to the 2D rGO/h-BN (hexagonal boron nitride) surface through facile electroprecipitation method. [80] Combining rGO with h-BN had generated defects that were utilized as nucleation sites for the growth of metal oxides. Furthermore, the loading of the heterostructure Fe 3 O 4 / NiO on the rGO/h-BN superlattice was tuned by applying different electrical bias.…”
Section: Carbon As Active Supportmentioning
confidence: 99%
“…To improve the electrode capacitance, pseudocapacitors (such as Ni(OH) 2 , Fe 3 O 4 , NiO, α-MnO 2 , and Ni 3 S 2 /NiS 2 ) have been added to BN-C-based composites. [74,[78][79][80][81] Nayak and coworkers focused on the characteristics of BN in supercapacitors with modifying polyaniline (PANI). [74] BN prevents the material from laminating and changes the surface morphology.…”
Section: Experimental and Applied Researchmentioning
confidence: 99%